Comparison of microwave ablation and surgical resection for treatment of hepatocellular carcinomas conforming to Milan criteria. Issue 7 (15th July 2014) - Shi, Jingxiang; Sun, Quan; Wang, Yijun; Jing, Xiang; Ding, Jianmin; Yuan, Qiang; Ren, Chaoyi; Shan, Shigang; Wang, Yandong; Du, Zhi
Abstract Background and Aim To compare the efficacy of microwave ablation (MWA) and surgical resection (RES) in the treatment of hepatocellular carcinoma (HCC) conforming to Milan criteria. Methods Two hundred twenty‐four patients met the inclusion criteria and were enrolled in the study. One hundred and seventeen patients received MWA, and 107 patients underwent RES. The primary endpoints were overall survival (OS) and disease‐free survival (DFS). Results The 1‐, 3‐, and 5‐year OS rates were 94%, 70%, 52% for the MWA group and 94%, 72%, 60% for the RES group (P = 0.513). The corresponding DFS rates for the two groups were 77%, 38%, 18% and 85%, 57%, 31% (P = 0.005). In subgroup analyses of patients with solitary HCC ≤ 3 cm, there were no significant differences in OS rates and DFS rates between the two groups (P = 0.577 and P = 0.140). For patients with solitary HCC 3 to 5 cm, there was no significant differences in OS rates between the two groups (P = 0.820), the DFS rates was significantly higher in the RES group than in the MWA group (P = 0.014). Conclusions MWA results in lower DFS rates than RES for HCC conforming to Milan criteria. However, the OS rates are comparable between the two therapies. For solitary HCC ≤ 3 cm, MWA is as effective as RES.